DETERMINASI KESADARAN WP EMKM KOTA PONTIANAK DALAM MEMENUHI KEWAJIBAN PERPAJAKAN - Khristina Yunita; Ira Grania Mustika; Tiya Nurfauziah (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2022)
This study trying to analyze the determination of WP EMKM to fulfill the taxation obligation. This study consists of three independent variables and one dependent variable. The independent variables in this study are understanding of tax regulations, tax officer services, and perceptions of indirect counter-achievement. The dependent variable in this study is taxation obligation. This research uses a survey method with WP EMKM as the respondents and already have tax id number. The results of the data analysis show that knowledge and understanding of taxes, tax officers services, and perceptions of counter-performance are simultaneously influence WP EMKM to fulfill their tax obligations.